ANALISIS KERAWANAN BENCANA BANJIR MENGGUNAKAN METODE PEMBOBOTAN DI SUB-DAS LUSI - Regina Larasati, Ajeng; Novita Sari, Dewi; Noor Anna, Alif; Ari Wibowo, Afif (Jurnal Spasial, 2025)
Floods are hydrometeorological disasters that frequently occur in Indonesia and cause significant impacts on social, economic, and environmental aspects. The Lusi Sub-watershed, which is part of the Serang Watershed in Central Java Province, has a high level of flood susceptibility due to high rainfall intensity, flat topography, and extensive land-use changes. This study aims to analyze the level of flood hazard in the Lusi Sub-watershed using the Analytical Hierarchy Process (AHP) weighting method and Geographic Information System (GIS). Nine parameters were used in the analysis, namely elevation, slope, curvature, Topographic Wetness Index (TWI), Normalized Difference Vegetation Index (NDVI), Land Use and Land Cover (LULC), distance to river, rainfall, and soil type. The weighting results show that rainfall has the highest influence with a weight of 25.4%, followed by distance to river (22.3%) and land use (10.3%). Based on spatial analysis, areas with moderate to high flood susceptibility dominate approximately 77.5% of the total area of the Lusi Sub-watershed, consisting of very low (1.02%), low (9.79%), moderate (41.44%), high (36.06%), and very high (1.75%) categories. Highly susceptible zones are concentrated in the central to western parts of the sub-watershed, particularly in Grobogan Regency.